(1)2x2-9x+8=0
(2)x2-2x=0
(3)x2-2x-3=0
(4)(2x-1)2=9
(5)(x+1)(x+2)=2x+4
(6)3x2-4x-1=0
(7)4x2-8x+1=0
(8)7x(5x+2)=6(5x+2)
(1)2x2-9x+8=0,
这里a=2,b=-9,c=8,
∵b2-4ac=81-64=17>0,
∴x=
,9± 17 4
则x1=
,x2=9+ 17 4
;9- 17 4
(2)x2-2x=0,
分解因式得:x(x-2)=0,
可得x=0或x-2=0,
解得:x1=0,x2=2;
(3)x2-2x-3=0,
分解因式得:(x-3)(x+1)=0,
可得x-3=0或x+1=0,
解得:x1=3,x2=-1;
(4)(2x-1)2=9,
开方得:2x-1=3或2x-1=-3,
解得:x1=2,x2=-1;
(5)(x+1)(x+2)=2x+4,
移项变形得:(x+1)(x+2)-2(x+2)=0,
即(x+2)(x-1)=0,
可得x+2=0或x-1=0,
解得:x1=-2,x2=1;
(6)3x2-4x-1=0,
这里a=3,b=-4,c=-1,
∵b2-4ac=16+12=28>0,
∴x=
=4±2 7 6
,2± 7 3
则x1=
,x2=2+ 7 3
;2- 7 3
(7)4x2-8x+1=0,
变形得:x2-2x=-
,1 4
配方得:x2-2x+1=
,即(x-1)2=3 4
,3 4
开方得:x-1=±
,3 2
∴x1=1+
,x2=1-3 2
;3 2
(8)7x(5x+2)=6(5x+2),
移项变形得:7x(5x+2)-6(5x+2)=0,
分解因式得:(5x+2)(7x-6)=0,
可得5x+2=0或7x-6=0,
解得:x1=-
,x2=2 5
.6 7